Conservation/Mutation in the Splice Sites of Cytokine Receptor Genes of Mouse and Human. (17th December 2013) - Calvello, Rosa; Cianciulli, Antonia; Panaro, Maria Antonietta
Abstract : Conservation/mutation in the intronic initial and terminal hexanucleotides was studied in 26 orthologous cytokine receptor genes of Mouse and Human. Introns began and ended with the canonical dinucleotides GT and AG, respectively. Identical configurations were found in 57% of the 5′ hexanucleotides and 28% of the 3′ hexanucleotides. The actual conservation percentages of the individual variable nucleotides at each position in the hexanucleotides were determined, and the theoretical rates of conservation of groups of three nucleotides were calculated under the hypothesis of a mutual evolutionary independence of the neighboring nucleotides (random association). Analysis of the actual conservation of groups of variable nucleotides showed that, at 5′, GTGAGx was significantly more expressed and GTAAGx was significantly less expressed, as compared to the random association. At 3′, TTTxAG and xTGCAG were overexpressed as compared to a random association. Study of Mouse and Human transcript variants involving the splice sites showed that most variants were not inherited from the common ancestor but emerged during the process of speciation. In some variants the silencing of a terminal hexanucleotide determined skipping of the downstream exon; in other variants the constitutive splicing hexanucleotide was replaced by another potential, in-frame, splicing hexanucleotide, leading to alterations of exon lengths.